Dynamics of substrate resource selection in network virtualization environment——an evolutionary game approach - Yu YANG; Shan-zhi CHEN; Xin LI (Tongxin xuebao)
The substrate network path selection problem of virtual network was modeled as an evolutionary game.In the process of evolutionary game,virtual networks adjusted the strategies through the iterated game.The replicator dynamics were leveraged equation to analyze the dynamic variation of strategies selection and demonstrates that this dynamics equation is the admissible dynamic to the evolutionary game.The potential game theory was used to analyze the evolutionary process and demonstrates the evolutionary result will converge to the evolutionary equilibrium.At the evolutionary equilibrium,all the virtual networks could get the best selection strategies.Finally,an evolutionary algorithm based on replicator dynamics was proposed.The experiments simulate the process of virtual network selecting the substrate paths in different initial state and reach the evolutionary equilibrium.Simulation results are coincided with the theoretical analysis results.